A Study of Relationship between Job Satisfaction and Organizational Climate of Principals of First Grade Degree Colleges of Hubli-Dharwad Corporation Area: Exploring the Impact of Job Satisfaction and Organizational Climate on Principals of First Grade Degree Colleges (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The purpose of the study is to A STUDY OF RELATIONSHIP BETWEEN JOB SATISFACTION AND ORGANIZATIONAL CLIMATE OF PRINCIPALS OF FIRST GRADE DEGREE COLLEGES OF HUBLI-DHARWAD CORPORATION AREA, The nature of present study is of descriptive survey. 50 First Grade Degree Colleges Principals of Hubli Dharwad Corporation area were selected for the study. The findings of the study concluded that Whenever job satisfaction increases it support to increase the self-rating scores, teacher educator skills, administrator skills, personnel administrator skills and public relation administrator skills of principals of First Grade Government Degree Colleges of Hubli-Dharwad Corporation area. Whenever the organizational climate increases it support to increases the self rating of principals, teacher-educator skills, administrator skills, personnel administrator, public relation administrator of principals of First Grade Government Degree Colleges of Hubli-Dharwad Corporation area.